An exploration of media repertoires in South Africa: 2002-2014 - Bakker, Hans-Peter (Department of Statistical Sciences, 2020)
This dissertation explores trends in media engagement in South Africa over a period from 2002 until 2014. It utilises data from the South African Audience Research Foundation’s All Media and Products Surveys. Using factor analysis, six media repertoires are identified and, utilising structural equation modelling, marginal means for various demographic categories by year are estimated. Measurement error is determined with the aid of bootstrapping. These estimates are plotted to provide visual aids in interpreting model parameters. The findings show general declines in engagement with traditional media and growth in internet engagement, but these trends can vary markedly for different demographic groups. The findings also show that for many South Africans traditional media such as television remain dominant.